Role of Protein Glycosylation in Candida parapsilosis Cell Wall Integrity and Host Interaction - Pérez-García, Luis A.; Csonka, Katalin; Flores-Carreón, Arturo; Estrada-Mata, Eine; Mellado-Mojica, Erika; Németh, Tibor; López-Ramírez, Luz A.; Toth, Renata; López, Mercedes G.; Vizler, Csaba; Marton, Annamaria; Tóth, Adél; et al. (Frontiers in Microbiology, 2016)
Candida parapsilosis is an important, emerging opportunistic fungal pathogen. Highly mannosylated fungal cell wall proteins are initial contact points with host immune systems. In Candida albicans, Och1 is a Golgi 1,6-mannosyltransferase that plays a key role in the elaboration of the N-linked mannan outer chain. Here, we disrupted C. parapsilosis OCH1 to gain insights into the contribution of N-linked mannosylation to cell fitness and to interactions with immune cells. Loss of Och1 in C. parapsilosis resulted in cellular aggregation, failure of morphogenesis, enhanced susceptibility to cell wall perturbing agents and defects in wall composition. We removed the cell wall O-linked mannans by -elimination, and assessed the relevance of mannans during interaction with human monocytes. Results indicated that O-linked mannans are important for IL-1 stimulation in a dectin-1 and TLR4-dependent pathway; whereas both, N- and O-linked mannans are equally important ligands for TNF and IL-6 stimulation, but neither is involved in IL-10 production. Furthermore, mice infected with C. parapsilosis och1 null mutant cells had significantly lower fungal burdens compared to wild-type (WT)-challenged counterparts. Therefore, our data are the first to demonstrate that C. parapsilosis N- and O-linked mannans have different roles in host interactions than those reported for C. albicans.